UJI TOKSISITAS DAN IDENTIFIKASI EKSTRAK SPONS Haliclona fascigera TERHADAP LARVA Artemia salina L. - Kadek Dewi Wirmandiyanthi; Manuntun Manurung; I Made Dira Swantara (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry), 2013)
The main purpose of this research is to determine the toxicity of sponge  Haliclona fascigera against larvae of Artemia salina and determine the compounds contained in the toxic isolates of sponge. The results showed chloroform fraction had the highest toxicity with LC50 of 63.10 ppm. Chloroform extracts were then separated by using eluent chloroform: ethyl acetate (8:2) and obtained five fractions. Based on the results of toxicity tests of the fifth fraction indicates the fraction 5 (F5) has the highest toxicity with LC50 of 89.13 ppm. Identification of toxic isolates F5 with GCMS show contained compound is 2-decenal, 3-eicosene, 6,10,14-trimethyl-2-pentadecanon, dibutyl-1,2-benzendikarboksilat, heksadekanoat acid, 4,8,12,16-tetramethylheptadecan-4-olide and dioctyl-1,2-benzendikarboksilat.